PEMBERIAN VERMIKOMPOS PADA PERTUMBUHAN BIBIT TANAMAN KAKAO (Theobroma cacao L.) - Rahmi Yulianda Fitri; Ardian Ardian; Isnaini Isnaini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This study aims to determine the effect and the best dose application of vermicompost on the growth of the cocoa plant seeds. The research was conducted at the experimental field of the Faculty of Agriculture, University of Riau, Tampan District, Pekanbaru. From May until August 2016. This study was conducted using a completely randomized design (RAL) non factorial with 6 treatments and three replications, in order to obtain 18 units of trial. Each experimental unit consisted of 3 seeds, so there are 54 seedlings. Parameters measured were seedling height, number of leaves, stem diameter, leaf area, the ratio of the canopy and root dry weight. Data were analyzed statistically using analysis of variance followed by fishers LSD test at level of 5%. The results showed that the dosing vermicompost fertilizer can improve seedling height, number of leaves, stem diameter, leaf area, dry weight and ratio of cacao seedling roots header. Vermicompost fertilizer dose of 10 ton / ha produced the highest growth in cocoa breeding. Keywords: cocoa, vermicompost